Deliverable Management In Projects (International Journal of Engineering and Computer Science, 2015)
: The purpose of this paper is to establish effective implementation of the WBS in projects. A case study of a hotel project is undertaken and analyzed for its WBS effectiveness and ways to lessen creep, uncertainty, risk and delays. This paper attempts to identify the use of deliverable oriented WBS for effective implementation. The research through the case study attempts to establish that WBS is not just a planning technique but a better control tool. It is also attempted to remove a common misconception that WBS is need for the contractor and client requires no active participation. The research attempts to identify various challenges associated with developing a quality WBS and suggest a methodology that can help practicing professionals in overcoming challenges and establish better control mechanisms in executing projects.